The unfulfilled promise of press freedom in Canada - Taylor, Lisa, 1968- (University of Toronto Press, 2017)
"The Unfulfilled Promise of Press Freedom in Canada offers a vast array of viewpoints that critically analyze the application and interpretation of press freedom under the Charter of Rights. This collection, assiduously put together by editors Lisa Taylor and Cara-Marie O'Hagan, showcases the insights of leading authorities in law, journalism, and academia as well as broadcasters and public servants. The contributors explore the ways in which press freedom has been constrained by outside forces, like governmental interference, threats of libel suits, and financial constraints. These intersectional and multifaceted lines of inquiry provide the reader with a 360-degree assessment of press freedom in Canada while discouraging complacency among Canadian citizens. After all, an informed citizenry is a free citizenry."--